2022
DOI: 10.1021/acs.jpclett.2c01580
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Lanthanide Atoms on Graphene: Similar, Yet Different

Abstract: Many theoretical studies address the interaction of different atoms with graphene; however, the relevant information on the adsorption of the lanthanide species remains limited and controversial, creating a gap in this important area of graphene chemistry and physics. By employing periodic density functional theory calculations, we provide the key theoretical information for the entire series from lanthanum to lutetium interacting with defect-free graphene, including the interaction strength and distances, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…While in the periodic calculations 19 the positive charge of most adsorbed Ln species was >1 e (except for Yb and Lu), in the study presented here the only such case is Eu, 1.092 e (Table 1 and the plot in Figure S2). Yb and Lu (0.234 and 0.287 e, respectively) exhibited again the lowest values of all.…”
Section: The Journal Of Physical Chemistry Letterscontrasting
confidence: 77%
See 4 more Smart Citations
“…While in the periodic calculations 19 the positive charge of most adsorbed Ln species was >1 e (except for Yb and Lu), in the study presented here the only such case is Eu, 1.092 e (Table 1 and the plot in Figure S2). Yb and Lu (0.234 and 0.287 e, respectively) exhibited again the lowest values of all.…”
Section: The Journal Of Physical Chemistry Letterscontrasting
confidence: 77%
“…Another possibility is that this phenomenon originates from the existence of a variable number of unpaired 4f electrons. In the latter regard, one should note that in our recent study 19 of Ln atom adsorption on a periodic graphene model (as well as in the previous related studies by other research groups 3,4,10,11,13,14 ), no visible distortion of the planar surface was reported.…”
supporting
confidence: 58%
See 3 more Smart Citations